2016
DOI: 10.1126/science.aaf7501
|View full text |Cite
|
Sign up to set email alerts
|

Increased plasmid copy number is essential for Yersinia T3SS function and virulence

Abstract: These authors share the last authorship *Correspondence to: tomas.edgren@umu.se; hans.wolf-watz@umu.se. Abstract:Pathogenic bacteria have evolved numerous virulence mechanisms that are essential for establishing infections. The enterobacteria, Yersinia, uses a Type III Secretion System (T3SS), encoded by a 70-kb, low-copy, IncFII-class virulence plasmid. Here, we report a novel virulence strategy in Y. pseudotuberculosis in which this pathogen up-regulates the plasmid copynumber during infection. We show that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
74
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 69 publications
(78 citation statements)
references
References 35 publications
4
74
0
Order By: Relevance
“…The ratio of repA transcripts to its antisense RNA copA was strongly increased compared with bacteria grown at 37°C. This transcriptional profile indicated that the replication of pYV is increased during Peyer's patch colonization and supported a recent observation showing that Yersinia up-regulates the pYV copy number during infection (69).…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…The ratio of repA transcripts to its antisense RNA copA was strongly increased compared with bacteria grown at 37°C. This transcriptional profile indicated that the replication of pYV is increased during Peyer's patch colonization and supported a recent observation showing that Yersinia up-regulates the pYV copy number during infection (69).…”
Section: Resultssupporting
confidence: 89%
“…Consequently, the most important defense mechanism of the bacteria is to adjust to the stressful conditions and counteract neutrophil attack within fibrin clots. Accordingly, the pathogen's transcriptional response is characterized by a marked up-regulation of the antiphagocytic T3SS/Yop machinery in response to temperature and an increase of the virulence plasmid copy number, which is likely triggered by host cell contact (69,96). This defense strategy is supported by the induction of radical detoxifying genes, such as hmp (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This variable sequencing depth challenges traditional k-mer filtering strategies based on a fixed, all-ornothing threshold. Additionally, it is critically important to recover such plasmids during sequencing, because increased copy number has been previously associated with virulence in other species like Yersinia pestis (Wang et al 2016). As expected, MHAP overlap sensitivity for the plasmid is low (26%) when repetitive k-mers are filtered via a fixed threshold.…”
Section: Adaptive Minhash K-mer Weightingmentioning
confidence: 84%
“…Bioluminescent in vivo imaging (BLI) allows the detection, visual characterization, and semiquantification of bacteria during infection of mice in real time (29). This method has widely been used to monitor Y. pseudotuberculosis YPIII infections using an in vivo imaging spectrum (IVIS) for BLI analysis (30)(31)(32)(33). To allow similar studies in strain IP32953, we constructed bioluminescent variants of the wild-type strain and the ΔtatC and ΔsufI mutant strains by integration of the complete lux operon from Photorhabdus luminescens into the 16S rRNA gene using a thermosensitive plasmid, p16Slux.…”
Section: Resultsmentioning
confidence: 99%